Wewenang Komisi Pemberantasan Korupsi dalam Penghentian Penyidikan dan Penuntutan Perspektif Independensi - Esmi Warassih Warassih Pudjirahayu; Faisal Faisal; Ndaru Satrio (Universitas Bengkulu, 2020)
The Corruption Eradication Commission (KPK) was formed independently, in its journey experiencing many changes, both in terms of the substance of the regulations and the institutional structure. The focus of this paper is the provisions of Article 40 of Law No. 19 of 2019 concerning Amendment to Law No. 30 of 2002 concerning the KPK. this research is a type of normative (doctrinal) research with prescriptive and applied nature which shows that the authority to stop the investigation and prosecution of the KPK based on Article 40 of Law No. 19 of 2019 concerning Amendment to Law No. 30 of 2002 concerning the KPK does not reflect the principle of independence which is a derivation of the Pancasila Legal Aspect Value. The first problem is that limiting the time for handling cases by the KPK will actually complicate the performance of the KPK itself. The second problem, it is possible to stop the investigation and prosecution based on the subjectivity of the KPK. The third problem is the estuary of all problems namely abuse of power.Komisi Pemberantasan Korupsi (KPK) dibentuk dengan sifat independen, dalam perjalanannya juga mengalami banyak perubahan, baik secara substansi peraturannya maupun secara struktur kelembagaannya. Adapun yang menjadi fokus kajian tulisan ini yaitu terkait ketentuan Pasal 40 UU No. 19 Tahun 2019 tentang Perubahan UU No. 30 Tahun 2002 tentang KPK. Jenis penelitian ini adalah normatif (doktrinal) dengan sifat preskriptif dan terapan, yang menunjukkan bahwa wewenang penghentian penyidikan dan penututan KPK berdasarkan Pasal 40 UU No. 19 Tahun 2019 tentang Perubahan UU No. 30 Tahun 2002 tentang KPK tidak mencerminkan asas independensi yang merupakan derivasi dari Nilai Cita Hukum Pancasila. Problematika yang pertama adalah membatasi waktu penanganan perkara yang dilakukan oleh KPK justru akan mempersulit kinerja KPK itu sendiri. Problematika kedua, sangat dimungkinkan penghentian penyidikan dan penuntutan ini dilandasi dengan alasan subjektifitas dari KPK. Problematika ketiga adalah muara dari semua permasalahan yaitu abuse of power.